ANALISIS SISTEM DAN PROSEDUR PENGELUARAN TENTANG PENERBITAN SURAT PERINTAH MEMBAYAR LANGSUNG (SPM-LS) PADA BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KOTA MANADO - Suneth, Reza Arfansyah; Sabijono, Harijanto; Mawikere, Lidia (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
This study discusses the Operating System and its Completion (SPM-LS) at the Regional Tax and Retribution Agency of Manado City. This research depends on the procedures and procedures on how to quickly (SPM-LS) because of the function of SPM-LS is the activity of work order from SKPD that is important to be studied. The purpose of this study is to find out how the system and procedures about the warrant that is in the agency tax and levy manado city and whether the system and procedures about the warrant is in conformity with SE.900 / 316 / BAKD. The method used in this research is descriptive, with qualitative approach. Results of research. Plans and payments. It is expected that the Regional Tax and Retribution Board of Manado City can improve and implement the system and procedures on Manado Regional Tax and Retribution Board of Manado City. Keywords: Letter pay Publishing, BP2RD, SPM-LS